2011
DOI: 10.1021/cg201300e
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the p-Toluenesulfonamide/Triphenylphosphine Oxide Crystal Chemistry: A New 1:1 Cocrystal and Ternary Phase Diagram

Abstract: A novel 1:1 cocrystal between p-toluenesulfonamide and triphenylphosphine oxide has been prepared and structurally characterized. This 1:1 cocrystal was observed to form during solid state grinding experiments, with subsequent formation of a known 3:2 cocrystal in the presence of excess sulfonamide. Both cocrystals are stable in the solid state. The ternary phase diagram for the two coformers was constructed in two different solvents: acetonitrile and dichloromethane. Examination of these diagrams clarified so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(61 citation statements)
references
References 25 publications
0
58
0
Order By: Relevance
“…Croker et al [13] using small scale experiments. In the current work, the mass fractions of p-TSA/TPPO/MeCN were varied according to the ternary phase diagram shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Croker et al [13] using small scale experiments. In the current work, the mass fractions of p-TSA/TPPO/MeCN were varied according to the ternary phase diagram shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Small scale batch co-crystallization studies (1 -50 mL) on the p-TSA-TPPO system have previous been reported [6], [13], [29]. The co-crystallization experiments were carried out in a 500 mL jacketed glass vessel fitted with an overhead PTFE pitch blade stirrer.…”
Section: Batch Co-crystallization Studymentioning
confidence: 99%
See 3 more Smart Citations